Handbook of water purity and quality - Ahuja, Satinder, 1933- (Academic Press, 2009)
This work provides those involved in water purification research and administration with a comprehensive resources of methods for analyzing water to assure its safety from contaminants, both natural and human-caused. The book first provides an overview of major water-related issues in developing and developed countries, followed by a review of issues of sampling for water analysis, regulatory considerations and forensics in water quality and purity investigations. The subsequent chapters cover microbial as well chemical contaminations from inorganic compounds, radionuclides, volatile and semivolatile compounds, disinfectants, herbicides, and pharmaceuticals including endocrine disruptors as well as potential terrorist-related contamination. The last chapter describes the Grainger prize-winning filter that can remove arsenic from water sources and sufficiently protect the health of a large number of people.-Covers the scope of water contamination problems on a worldwide scale.-Provides a rich source of methods for analyzing water to assure its safety from natural and deliberate contaminants.-Describes filter that won the million dollar Grainger price and thereby highlighting an important approach to remediation.